The Relationship Between Anxiety and Overactive Bladder or Urinary Incontinence Symptoms in the Clinical Population - Lai, H. Henry; Rawal, Amar; Shen, Baixin; Vetter, Joel (Urology (Ridgewood, N.J.), 2016)
To investigate the relationship between anxiety and overactive bladder (OAB) or urinary incontinence symptoms among clinical population. Patients who were diagnosed with OAB and age-matched control subjects without OAB were enrolled. Anxiety symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS-A). OAB or incontinence symptoms were assessed using the International Consultation on Incontinence—Urinary Incontinence Short Form (ICIQ-UI), ICIQ-OAB, Urogenital Distress Inventory Short Form (UDI-6), Incontinence Impact Questionnaire Short Form (IIQ-7), and OAB-q. Other psychosocial factors were also assessed. About half of the OAB subjects (48%) had anxiety symptoms, and one quarter of OAB subjects (24%) had moderate to severe anxiety. OAB subjects reported significantly higher anxiety symptoms compared to age-matched controls (HADS-A: 7.5 ± 4.5 vs 3.3 ± 3.6, P < .001). OAB subjects with anxiety reported more severe OAB or incontinence symptoms, and greater bother and impact on quality of life compared to OAB subjects without anxiety (ICIQ-UI, ICIQ-OAB, UDI-6, IIQ-7, OAB-q, P values all <.05). OAB subjects with anxiety also have more psychosocial difficulties (eg, more depression, higher stress levels). Among OAB subjects, there were positive correlations between the severity of anxiety symptoms and the severity of OAB/incontinence symptoms (Spearman's correlation coefficients 0.29 to 0.47, P < .05). OAB subjects with both anxiety and depression reported higher ICIQ-UI and IIQ-7 scores than those who had anxiety but no depression (P = .014, .025 respectively). OAB patients reported higher anxiety symptoms compared to controls. OAB patients with anxiety reported more severe OAB or incontinence symptoms, worse quality of life, and more psychosocial difficulties compared to OAB patients without anxiety. There are positive correlations between the severity of anxiety symptoms and OAB or incontinence symptoms.